Fluid Mechanics with Civil Engineering Applications, Eleventh Edition - Finnemore, E. John; Maurer, Ed (McGraw-Hill's AccessEngineeringLibrary., 2024)
This eleventh edition of the classic textbook, Fluid Mechanics with Civil Engineering Applications, continues and improves on its tradition of explaining the physical phenomena of fluid mechanics and applying its basic principles in the simplest and clearest possible manner without the use of complicated mathematics. It focuses on civil, environmental, and agricultural engineering problems, although mechanical engineering topics are also strongly represented. The book is written as a text for a first course in fluid mechanics for civil and related engineering students, with sufficient breadth of coverage that it can serve in a number of ways for a second course if desired.